The Application of Distance Learning (DAD) during the Covid-19 Emergency for Students with certified Disabilities. An Exploratory Investigation - Mulè, Paolina (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
In this contribution, after a brief introduction on the Covid-19 emergency scenario, that has come to be determined, starting from the first months of 2020, and after reflecting on the theoretical framework of reference and on the in-service training course addressed to the Teacher Tutor Coordinators of the School for Disability of the Inclusion Pole of Catania“ Italo Calvino”, we want to present the data of an exploratory survey, on the application of distance learning to students with certified disabilities, which involved 2993 teachers between curricula and support of the Inclusion Center of Catania and the Province. From the exploratory survey it emerges that there is still a need to strengthen the in-service training of curricular and support teachers regarding the application of integrated digital teaching, as well as the knowledge of new active and collaborative methodologies aimed at building personalized and class-based training courses in an inclusive perspective.